PEMBUATAN WEBSITE DESA SEBAGAI SARANA DIGITALISASI ADMINISTRASI DAN ARSIP SURAT MASUK–KELUAR DI DESA MOJOPARON - Fachrur Rozieq Maulana (COMVICE: Journal Of Community Service, 2025)
The development of information technology has accelerated digital transformation across various sectors, including village governance. However, most villages in Indonesia still face challenges in managing administrative processes and document archiving systematically. This Community Service Program (PKM) aims to assist the Mojoparon Village Government, Rembang District, Pasuruan Regency, in developing a village website as a digital information system to centrally manage incoming and outgoing letters as well as documentation of village activities. The implementation methods include needs analysis, web system design using the PHP–MySQL framework, training for village operators, and pilot implementation testing. The results indicate that the developed website successfully streamlined administrative processes, improved archiving efficiency, and strengthened transparency in public services. This program serves as an initial step toward e-government-based village governance that is adaptive to the digital era.